The Dynamics of Educational Services in the Decentralization Era in Lampung Timur Regency - Jannata, Pandu Farchan; Mardiansjah, Fadjar Hari (Department of Urban and Regional Planning, Universitas Diponegoro, 2021)
Lampung Timur Regency is one of the regencies in the Province of Lampung, which was established in 1999, just before the implementation of the decentralization era in Indonesia. The regency has been detached from its “core district”, the Regency of Lampung Tengah. There has been an expectation that it will lead to more efficient and effective services and equal development in its region. This paper evaluates the delivery of educational services involving elementary, middle, and high schools during the decentralization era from 2000 to 2015. Using the time serial statistical data gathered from the district’s monographs and the standard set by the National Standard, this paper analyzes the availability of the services using inter-time and inter-regional comparisons and the combination of both comparisons. The result shows that during this period, the local government of Lampung Timur Regency focused on improving middle school than elementary and high school services. The case deems that transferring high school authority at the provincial level does not guarantee the effectiveness of improving high school services in the regency.